Complete Genome Sequence of an Alkane Degrader, Alcanivorax sp. Strain NBRC 101098 - Miura, Takamasa (American Society for Microbiology, 2014)
Alcanivorax sp. strain NBRC 101098 was isolated from seawater in Japan. Strain NBRC 101098 is able to degrade various types of n-alkanes. Here, we report the complete genome of strain NBRC 101098.